One Economics, Many Recipes : Globalization, Institutions, and Economic Growth - Rodrik, Dani (Book collections on Project MUSE., 2007)
In One Economics, Many Recipes, leading economist Dani Rodrik argues that neither globalizers nor antiglobalizers have got it right. While economic globalization can be a boon for countries that are trying to dig out of poverty, success usually requires following policies that are tailored to local economic and political realities rather than obeying the dictates of the international globalization establishment. A definitive statement of Rodrik's original and influential perspective on economic growth and globalization, One Economics, Many Recipes shows how successful countries craft their own.